(untitled) (Contemporary Journal of Social Science Review, 2025)
There are a large number of non-Muslim biographers who have studied the biography of the Prophet Muhammad (peace be upon him). Some non-Muslims have similar views on the biography, while others have different views, which clearly shows a contradiction in their views. The most important weapon of non-Muslim biographers in studying the biography is their critical attitude. The aim of the critical attitude was to cast doubt on the religion of Muslims, so that Muslims would hate their own religion. Non-Muslim biographers have interpreted the state of revelation, which is a divine law for the human race, as epileptic seizures, although this is a hypothetical assumption of theirs that has been fabricated and has no basis in fact. Thus, the Prophet Muhammad (peace and blessings of Allah be upon him) has been criticized for inventing a new religion, for wanting to gain a special status for himself. Objecting to the sources of knowledge of the Prophet (peace and blessings of Allah be upon him), the source of the Prophet’s teachings has been declared to be the teachings of the Christians. He did not acquire his knowledge of religion from the Christians. The Prophet’s prophethood has also been cast into doubt, and it has been said that he had doubts about his being a messenger. Non-Muslim biographers have also accused the Prophet (peace and blessings of Allah be upon him) of worshipping other than Allah, and that he gave a place to idolatry in Islam. The religious matters in the biography of the Prophet Muhammad (peace be upon him) are of great importance. Objecting to them is like demolishing the building of Islam, and these people did so to make Islam doubtful, so that people would become disgusted with Islam and the Prophet of Islam. In this discussion, the criticism of non-Muslim biographers on religious matters related to the biography has been analyzed along with arguments.